Functional complementarity and specialisation: The role of biodiversity in plant–pollinator interactions - Blüthgen, Nico; Klein, Alexandra-Maria (Basic and applied ecology, 2011)
Ecological niche breadth (specialisation) and niche differentiation (complementarity) play a key role for species coexistence and hence biodiversity. Some niche dimensions of a species represent ecosystem functions or services such as pollination (functional niche). When species differ in their contribution to some collective function (functional complementarity), this implies that functions from several species are required for a high overall functional performance level. Applied to plant–pollinator interactions, functional complementary suggests that a higher diversity of pollinators contributes to an increased pollination success of the plants or, in turn, that a higher diversity of flowers may better sustain the consumers’ requirements. Complementarity can affect functioning at different scales: the collective functioning of the target community, a single species, an individual or even a part of the individual, e.g. a single flower. Recent network analyses revealed that plant–pollinator interactions display a relatively high extent of complementary specialisation at the community scale. We propose several mechanisms that generate complementarity. From the consumers’ viewpoint, differences in flowering phenology and/or nutritional variation in floral resources (nectar, pollen) may explain a complementary role of different flower species. From the plant's viewpoint, temporal or environmental variation in the pollinator species’ activities may contribute to complementary effects on pollination of plant communities. In addition, different species may also pollinate either more exposed or more sheltered flowers from the same plant individual, or vary in their functions within single flowers. So far, empirical evidence for complementary effects in general, and particularly mechanistic explanations of such effects are scant and will require comparative investigations at multiple scales in the future. Such studies will help us to understand if and how biodiversity maintains the quality and quantity of plant–pollinator functional relationships. Nischendifferenzierung (Komplementarität) und ökologische Nischenbreite (Spezialisierung) spielen eine Schlüsselrolle in der Koexistenz von Arten und demzufolge für die Biodiversität. Einige Nischendimensionen von Arten bilden Ökosystemfunktionen (funktionale Nische) wie z.B. Bestäubung. Wenn Arten sich in ihrem funktionellen Beitrag unterscheiden (funktionale Komplementarität), lässt das darauf schließen, dass artenreiche Gemeinschaften insgesamt leistungsfähiger als artenarme Gemeinschaften sind. Bezogen auf die Interaktionen von Blüten und Bestäubern impliziert funktionale Komplementarität, dass eine größere Artenvielfalt der Bestäuber zu einer besseren Bestäubung der Pflanzenarten beiträgt und umgekehrt eine größere Blütenvielfalt besser die Ansprüche der Bestäuberarten deckt. Komplementarität kann bei unterschiedlichen Skalen ansetzen und die kollektive Funktion der Gemeinschaft beeinflussen, die Funktion einer einzigen Art, eines Individuums oder sogar nur eines Teils eines Individuums, z.B. einer einzelnen Blüte. Neuere Netzwerkanalysen zeigen eine stark ausgeprägte Komplementarität der Interaktionen zwischen Pflanzen- und Bestäuberarten auf Gemeinschaftsniveau. Wir fassen unterschiedliche Mechanismen zusammen, die Komplementarität hervorbringen. Aus der Sicht des Konsumenten können Unterschiede in der Phänologie oder Unterschiede in den Nährstoffressourcen der Blüten (z.B. Nektar, Pollen) eine komplementäre Rolle mehrerer Pflanzenarten erklären. Aus der Sicht der Pflanze können zeitliche oder wetterbedingte Aktivitätsunterschiede der Bestäuberarten zu komplementären Effekte bei der Bestäubung beitragen. Außerdem können verschiedene Tierarten unterschiedlich räumlich verteilte Blüten eines Pflanzenindividuums bestäuben oder sich die Funktion innerhalb einer Blüte aufteilen. Bis heute sind empirische Nachweise komplementärer Effekte und mechanistische Erklärungen für solche Effekte selten untersucht worden. Zukünftige vergleichende Untersuchungen zu Komplementaritätseffekten sollten verschiedene Skalen berücksichtigen. Solche Studien können zum Verständnis beitragen, ob und wie Artenvielfalt die Qualität und Quantität der funktionellen Beziehungen zwischen Blüten und Bestäubern fördert.